2018
DOI: 10.1111/pce.13476
|View full text |Cite
|
Sign up to set email alerts
|

Smells from the desert: Microbial volatiles that affect plant growth and development of native and non‐native plant species

Abstract: The plant microbiota can affect host fitness via the emission of microbial volatile organic compounds (mVOCs) that influence growth and development. However, evidence of these molecules and their effects in plants from arid ecosystems is limited. We screened the mVOCs produced by 40 core and representative members of the microbiome of agaves and cacti in their interaction with Arabidopsis thaliana and Nicotiana benthamiana. We used SPME‐GC‐MS to characterize the chemical diversity of mVOCs and tested the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 68 publications
(97 reference statements)
0
50
0
1
Order By: Relevance
“…However, it was Sánchez-López et al (2016a) who truly demonstrated the generality of this microbial capacity to change plant performance through VOC emissions by testing 13 bacterial and 17 fungal phylogenetically diverse isolates, encompassing saprotrophs, beneficials and phytopathogens as well as microbes that normally do not interact with plants. In line with this finding, Camarena-Pozos et al (2019) recently revealed that approximately 90% of 40 agave- and cactus-associated bacterial strains promoted growth and development of Arabidopsis and Nicotiana benthamiana via the emission of volatiles.…”
Section: Introductionmentioning
confidence: 54%
“…However, it was Sánchez-López et al (2016a) who truly demonstrated the generality of this microbial capacity to change plant performance through VOC emissions by testing 13 bacterial and 17 fungal phylogenetically diverse isolates, encompassing saprotrophs, beneficials and phytopathogens as well as microbes that normally do not interact with plants. In line with this finding, Camarena-Pozos et al (2019) recently revealed that approximately 90% of 40 agave- and cactus-associated bacterial strains promoted growth and development of Arabidopsis and Nicotiana benthamiana via the emission of volatiles.…”
Section: Introductionmentioning
confidence: 54%
“…Moreover, members of this genus also exert positive effects on the health and growth of different plants (Hornschuh et al, 2002;Abanda-Nkpwatt et al, 2006;Hellmuth and Kutschera, 2008;Madhaiyan et al, 2009;Tani et al, 2012;Kwak et al, 2014;Madhaiyan and Poonguzhali, 2014;Krishnamoorthy et al, 2018). Contrary to native plants, in the phyllosphere of A. tequilana from Amatitan the main AAP bacteria were the genus Belnapia (Rhodospirillales) that has also been linked to AAP in desert microbial crusts (Csotonyi et al, 2010) and to growth promotion of A. thaliana (Camarena-Pozos et al, 2019). We propose that AAP Methylobacterium and Belnapia can be effective colonizers of the agave and cacti phyllosphere due to their ability to utilize both chemical and luminous energy, and also influence the growth and health of agaves and cacti.…”
Section: Phototrophy Is a Signature Trait Of The Phyllosphere Of Agavmentioning
confidence: 99%
“…have been isolated and characterized from the rhizosphere, root and leaf endosphere, phyllosphere and seeds of A. tequilana, Agave salmiana, Myrtillocactus geometrizans and Opuntia robusta (Desgarennes et al, 2014;Fonseca-García et al, 2016). Most of these strains also produced a diverse mixture of organic volatile compounds that promote the growth of A. thaliana, Nicotiana benthamiana, A. tequilana and A. salmiana, including novel and known compounds which biological activity was cryptic (Camarena-Pozos et al, 2019). These studies highlighted the contribution of the agave and cacti microbiome to plant fitness and the importance of studying the microbiome of nonmodel plants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bacillus and Pseudomonas strains were reported to produce 2,3-butanediol, acetoin, 2-butanone, 2-methyl-n-1-tridecene, albuterol, 1,3 propane-di-ol, and dimethyl disulfide (DMDS), which improved the growth of plants by interfering with plant hormone signaling and induced systemic resistance against plant pathogens 6,[8][9][10][11] . Recently, MVCs, mainly consisting of benzyl alcohol, propanol, butanol, and other sulfur-containing compounds, were reported to improve the growth of Arabidopsis, Nicotiana, and agaves 8,12 . The root system of Arabidopsis was modulated upon exposure to the volatile DMDS, which affected the canonical auxin signaling pathway 13 .…”
mentioning
confidence: 99%